Execution Of Court Decisions In The Form Of Confirmation Of Narcotics Evidence For The State (Case Study Of Execution Of Decision No 39/Pid.Sus/2020/PN, BYL) - Oki Suwandi; Natangsa Surbakti; Muchamad Iksan (Publikasi Indonesia, 2023)
This research examines the perspective on the execution of court decisions on narcotics evidence confiscated for the state. The purpose of this study is to find out the implementation of the execution of seized narcotics evidence for the State in terms of criminal law and Narcotics Law. The research uses empirical and juridical approach methods. The execution of the court's decision on narcotics evidence is contained in ruling No. 39/Pid.Sus/2020/PN.BYL stated that the narcotics evidence seized is for the state. The destruction of evidence of narcotics is regulated in Law Number 35 of 2009 concerning Narcotics, and the Attorney General's decision number: KEP-089/J.A/1988 concerning Settlement of Confiscated Goods in Articles 12 to 14. The results of this study show how the mechanism for completing the process of confiscation of seized narcotics evidence for the state is viewed from the perspective of criminal law. This researcher wants to explain what is the mechanism for implementing criminal case decisions regarding seized narcotic evidence for the State. Judging from the importance of destroying narcotics confiscated goods, it is necessary to know the procedure for destroying narcotics confiscated goods so that they are more in line with the procedures described in the law. As stated that the purpose of administering criminal procedural law in Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) is to achieve and obtain or at least approach material truth (substantial truth) namely the complete truth of a criminal incident by applying the provisions of criminal procedure law honestly and appropriately.